Molecular cloning of a member of a third class of Shaker-family K+ channel genes in mammals. - McCormack, T (1991)
In the human proteolipid protein gene, the base sequence of the intronic region 5' to exon 6 was found to be 5'-ctctttcattttcctgcag-3' and not 5'-ctctttt-cattttcctgcag-3' as previously reported.